Patients with lesions to left prefrontal cortex (BA 9 and BA 10) have less entrenched beliefs and are more skeptical reasoners - Goel, V; Marling, M; Raymont, V; Krueger, F; Grafman, J (Massachusetts Institute of Technology Press, 2019)
The effect of prior beliefs on reasoning and decision-making is a robust, poorly understood phenomenon, exhibiting considerable individual variation. Neuroimaging studies widely show the involvement of the left pFC in reasoning involving beliefs. However, little patient data exist to speak to the necessity and role of the left pFC in belief-based inference. To address this shortcoming, we tested 102 patients with unilateral focal penetrating traumatic brain injuries and 49 matched controls. Participants provided plausibility ratings (plausible/implausible) to simple inductive arguments and (separately) strength of believability ratings of the conclusion to those same arguments. A voxel-based lesion symptom mapping analysis identified 10 patients, all with lesions to the left pFC (BA 9 and BA 10) as rating significantly fewer arguments with highly believable conclusions as "plausible," compared with all other patients. Subsequent analyses, incorporating the right hemisphere homologue of these patients (n = 12) and normal controls (n = 24), revealed patients with lesions to left pFC found fewer arguments plausible in the high believable than either of these groups, and there was no difference in the behavioral scores of the right pFC patients and normal controls. Further analysis, utilizing the belief ratings as the dependent measure, revealed a Group × Belief Rating interaction, with left pFC patients having less intense beliefs about the conclusions of moderately believable and highly believable arguments. We interpreted these results to indicate that lesions to left pFC (BA 9, BA 10) increase incredulity and make these patients more skeptical reasoners. The former can partially, but not fully, explain the latter. The other relevant factor may be that unilateral left pFC lesions disrupt hemispheric equilibrium and allow for an increased inhibitory role of the right pFC. We speculate that individual differences in belief bias in reasoning in the normal population may be a function of individual differences in the left and right pFC interactional dynamics.